2020
DOI: 10.3389/fpsyg.2020.601724
|View full text |Cite
|
Sign up to set email alerts
|

My Brain Needs a Break: Kindergarteners’ Willpower Theories Are Related to Behavioral Self-Regulation

Abstract: Is the way that kindergarteners view their willpower – as a limited or as a non-limited resource – related to their motivation and behavioral self-regulation? This study is the first to examine the structure of beliefs about willpower in relation to behavioral self-regulation by interviewing 147 kindergarteners (52% girls) aged 5 to 7 years (M = 6.47, SD = 0.39). A new instrument was developed to assess implicit theories about willpower for this specific age group. Results indicated that kindergarteners who th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…In terms of the research approach of implicit theories (Dweck, 1999), MoBs could be viewed as incremental beliefs that athletic ability is achieved by willpower, enduring pain and investing effort. This interpretation fits with Job and colleagues findings that an incremental belief about one´s willpower (willpower is not limited) predicts better behavioral self-regulation than the belief that willpower is a limited resource that can deplete and needs time to be filled up (Bernecker & Job Sutnar, 2020;Compagnoni et al, 2020;Francis et al, 2021). One advantage of considering MoBs in the theoretical framework of implicit beliefs is that approaches to changing beliefs are already being developed.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of the research approach of implicit theories (Dweck, 1999), MoBs could be viewed as incremental beliefs that athletic ability is achieved by willpower, enduring pain and investing effort. This interpretation fits with Job and colleagues findings that an incremental belief about one´s willpower (willpower is not limited) predicts better behavioral self-regulation than the belief that willpower is a limited resource that can deplete and needs time to be filled up (Bernecker & Job Sutnar, 2020;Compagnoni et al, 2020;Francis et al, 2021). One advantage of considering MoBs in the theoretical framework of implicit beliefs is that approaches to changing beliefs are already being developed.…”
Section: Discussionsupporting
confidence: 72%
“…In a study by Alavi et al (2019) examining factors related to academic achievement, they found that girls had higher levels of attention skills and better impulse control compared to boys. Compagnoni et al (2020) investigated the relationship between children's behavioral self-regulation skills and motivation levels in a sample of 147 preschool children aged 5 to 7 years. The results indicated that girls showed better behavioral self-regulation skills compared to boys.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Further research may also take a close look at moderating processes that play an important role at several points within the schema model of self-control (see the white boxes in Figure 1). For instance, people's implicit theories of whether willpower is a limited or an unlimited resource (Job et al, 2010;Compagnoni et al, 2020) can influence how perceived self-control demands are related to affective experiences (Konze et al, 2018). Another relevant moderating influence may be the extent to which individuals feel autonomous during a self-control demand.…”
Section: Discussionmentioning
confidence: 99%